2014
DOI: 10.1155/2014/828162
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Disease Prevalence in a Multiple Sclerosis Cohort in Argentina

Abstract: Background. Comorbid autoimmune diseases in MS patients have been studied extensively with controversial results. Moreover, no such data exists for Latin-American MS patients. Methods. We conducted a case-control study aimed to establish the prevalence of autoimmune disorders in a cohort of Argentinean MS patients. Results. There were no significant differences in autoimmune disease prevalence in MS patients with respect to controls. The presence of one or more autoimmune disorders did not increase risk of MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…Autoimmune diseases are a common occurrence in patients in MS, as the present study shows, in agreement with previous reports (9.4%) 5,11 . Our series showed autoimmune thyroiditis as the most frequent concurrent diagnosis (n = 15/635), which was already reported [11][12][13][14][15] (4/155, 20/199, 106/314, 97/815, 53/286), psoriasis 4 (6/24), asthma 16 (8%), type 1 diabetes mellitus 5 (9/245) and inflammatory bowel disease 6 were the most frequently found AID in other cohorts, and were also featured in the present cohort.…”
Section: Discussionsupporting
confidence: 84%
“…Autoimmune diseases are a common occurrence in patients in MS, as the present study shows, in agreement with previous reports (9.4%) 5,11 . Our series showed autoimmune thyroiditis as the most frequent concurrent diagnosis (n = 15/635), which was already reported [11][12][13][14][15] (4/155, 20/199, 106/314, 97/815, 53/286), psoriasis 4 (6/24), asthma 16 (8%), type 1 diabetes mellitus 5 (9/245) and inflammatory bowel disease 6 were the most frequently found AID in other cohorts, and were also featured in the present cohort.…”
Section: Discussionsupporting
confidence: 84%
“…After deleting duplicate records and screening the abstracts and titles, 70 articles were selected for full‐text assessment. Ultimately, 17 studies 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 were included in the meta‐analysis. A flow diagram of the search results and study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an inflammatory disorder of the brain, spinal cord, and optic nerves with unknown etiology arising as a result of complex interactions between genetic and environmental factors [1][2][3]. It affects twice as many women as men and typically develops between the ages of 20 and 40 years (the average age of MS onset is 30 years) [4].…”
Section: Introductionmentioning
confidence: 99%